FC 132SHORT COURSE DAILY LOW-DOSE PREDNISOLONE AT THE TIME OF UPPER RESPIRATORY TRACT INFECTION (URTI) IN NON-SELECTED CHILDREN WITH RELAPSING STEROID SENSITIVE NEPHROTIC SYNDROME DOES NOT PREVENT URTI-RELATED RELAPSE: THE PREDNOS 2 TRIAL. (29th May 2021) - Christian, Martin; Webb, Nicholas; Mehta, Samir; Nafsika, Afentou; Woolley, Rebecca; Frew, Emma; Brettell, Elizabeth; Khan, Adam; Milford, David; Bockenhauer, Detlef; Saleem, Moin A; Hall, Angela; et al.
Abstract: Background and Aims: At least 80% of children with steroid sensitive nephrotic syndrome (SSNS) have relapses and many are triggered by upper respiratory tract infections (URTIs). Previous small studies (4 studies, 232 patients in total), mostly in children already taking maintenance corticosteroid in countries where URTI epidemiology is different to Europe, showed that giving daily low-dose prednisolone for 5-7 days during an URTI reduces the risk of relapse. The objective of the PREDNOS 2 trial was to determine if these findings were replicated in a large UK population of children with relapsing SSNS on different background medication or none. Method: A randomised, double-blind, placebo-controlled trial, including a model-based economic evaluation was carried out in 122 UK paediatric departments. Between February 2013 and January 2019, 365 children with relapsing SSNS (mean age: 7.6 ± 3.5 y) were recruited from 91 sites and randomised (1:1) according to a minimisation algorithm based on background treatment (no background treatment; low-dose prednisolone only; low-dose prednisolone and other immunosuppression; other immunosuppression only). At the start of an URTI, children received 6 days of prednisolone 15 mg/m2 or matching preparation of placebo. Those already taking alternate day prednisolone rounded their daily dose using trial medication to the equivalent of 15 mg/m2 or their alternate-day dose, whichever was the greater. The primary outcome was the incidence of first URTI-related relapse (URR) following any URTI over 12 months. Secondary outcomes were the overall rate of relapse, changes in background treatment, cumulative dose of prednisolone, rates of serious adverse events, incidence of corticosteroid adverse effects, change in Achenbach Child Behaviour Checklist score and quality of life. Analysis was by intention to treat. The economic evaluation used trial data and a decision-analytic model to estimate Quality-Adjusted-Life-Years (QALYs) and costs at 1-year, which were then extrapolated over 16 years. Results: 80 children completed 12 m follow-up without an URTI. Consent was withdrawn for 32 children, 14 prior to an URTI, leaving a modified intention to treat analysis population of 271 children (134 and 137 in prednisolone and placebo arms respectively). There were 384 URTIs and 82 URRs in the prednisolone arm, and 407 URTIs and 82 URRs in the placebo arm. The number of patients experiencing a URR was 56 (42.7%) and 58 (44.3%) in the prednisolone and placebo arms respectively (adjusted risk difference: -0.024, 95% CI: -0.14 to 0.095; P=0.7). There was no evidence that the treatment effect differed when data were analysed according to background treatment. There were no significant differences in secondary outcomes between treatment arms. A post-hoc subgroup analysis assessing primary outcome in 58 children of South Asian ethnicity (RR 0.66, 95% CI: 0.396 to 1.105) versus 213 of other ethnicity (RR 1.11, 95% CI: 0.806 to 1.535) showed possible efficacy of intervention in those of South Asian ethnicity (test for interaction P=0.09). Giving daily prednisolone at the time of an URTI was found to increase QALYs and decrease overall costs, when compared to standard care, a finding that was robust to sensitivity analysis. Conclusion: In a large and methodologically-robust study, PREDNOS 2 has shown that giving 6 days of daily low-dose prednisolone at the time of an URTI does not reduce the risk of relapse of nephrotic syndrome in UK children, but could offer a cost-effective use of health care resources. Further work is needed to investigate inter-ethnic differences in treatment response, and the pathogenesis of individual viral infections and their effect on nephrotic syndrome.